2021
DOI: 10.1071/sh20176
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of pelvic inflammatory disease and barriers to conducting pelvic examinations in Australian general practice: findings from an online survey

Abstract: Background Pelvic inflammatory disease (PID) is under-diagnosed globally, particularly in primary care, and if untreated may cause reproductive complications. This paper investigates PID diagnosis by Australian general practitioners (GPs) and barriers to their conducting a pelvic examination. Methods: An online survey investigating Australian GPs’ chlamydia management, including PID diagnosis, was conducted in 2019. From 323 respondents, 85.8% (n = 277) answered multiple-choice questions about PID and 74.6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…All clinicians acknowledged that there is a degree of uncertainty when diagnosing PID, and some considered how diagnosis can be especially challenging for clinicians with less experience. This perception is reflected in other literature; some Australian clinicians who infrequently perform bimanual pelvic examinations have reported low levels of confidence in interpreting findings, [ 9 ] and less experienced clinicians have demonstrated lower levels of diagnostic ability for PID [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All clinicians acknowledged that there is a degree of uncertainty when diagnosing PID, and some considered how diagnosis can be especially challenging for clinicians with less experience. This perception is reflected in other literature; some Australian clinicians who infrequently perform bimanual pelvic examinations have reported low levels of confidence in interpreting findings, [ 9 ] and less experienced clinicians have demonstrated lower levels of diagnostic ability for PID [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is unsurprising, as clinicians who responded to the study advertisement are likely to have been interested in sexual and reproductive health. We interviewed only one male clinician and it is clear that male GPs face additional barriers to conducting pelvic examinations; our previous research found male GPs less likely to perform pelvic examinations on symptomatic women than female GPs [ 9 ]. Our findings are therefore not generalisable to all Australian primary care clinicians, and we were not able to explore the perspectives of clinicians working in a wide range of clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PID is predominantly diagnosed according to clinical signs and symptoms; however, clinical diagnosis can be challenging due to the diverse range of clinical presentations. A more definitive investigation such as laparoscopy is considered a more invasive and resource‐intensive test, and usually not requested in general practice unless for more complicated infections with poor treatment response 17 . Further, many general practitioners cite that the need for a pelvic examination can be a barrier to diagnosis 17 …”
Section: Improve Diagnosis Of Pelvic Inflammatory Diseasementioning
confidence: 99%
“… 9 20 While acknowledging the risk for PID is likely to be higher for women attending sexual health clinics, other Australian data show general practitioners (GPs) have expressed hesitancy in conducting pelvic examinations to support a PID diagnosis, potentially reducing their capacity to diagnose PID. 21 Interventions for strengthening chlamydia management (eg, mailed specimen kits, links to partner notification websites in chlamydia test results) have improved retesting and uptake of partner notification discussions in specialist sexual health and family planning clinics. 22 23 Patient-delivered partner therapy (PDPT), a method of expediting partner treatment, has been shown to be effective at reducing reinfection and acceptable to patients and partners.…”
Section: Introductionmentioning
confidence: 99%